PENGARUH PERPUTARAN PIUTANG USAHA DAN PERPUTARAN PERSEDIAAN TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BEI - B11108078, Yohanes Gabriel H (Jurnal Manajemen Update, 2013)
ABSTRACTThe objective of the research is finding out whether the Account Receivable Turnover and Inventory Turnover influence the profitability both partially and stimulatingly. The object chosen by the researcher is automotive industry companies which components are registered on Indonesian Stock Exchange. Research method on this thesis is Causal Research; with the number of samples is 10 companies from 19 automotive industry companies registered on Indonesian Stock Exchange. The research is conducted for the observation in 2006-2010. The type of data is seconder data. The data is gathered from Indonesian Stock Exchanges official site and ICMD. Then collected data is analyzed by using data analysis method, which has been tested with classical assumption before the hypothesis testing. Hypothesis testing in this research uses double linear regression analysis with t testing and f testing on the significant level of 5% (? = 0,05). The result of Hypothesis testing shows that Partial Variable of Account Receivable Turnover is influential against Profitability and Inventory Turnover has positive influence, but not significant, against Profitability. Stimulatingly, Account Receivable Turnover and Inventory Turnover is influential against profitability. Where 12% of variation from profitability changes can be explained by the variation of both of independent variable, whereas the rest, on the number of 88% is explained by the variation and other factors which are not including on the regression model. Keywords: Account Receivable turnover, Inventory turnover and profitability.